2008
DOI: 10.21913/ijei.v4i2.412
|View full text |Cite
|
Sign up to set email alerts
|

Does culture influence understanding and perceived seriousness of plagiarism?

Abstract: This paper discusses the perceived seriousness and understanding of plagiarism by local and Asian international students in Australia, presenting new data from a study conducted at two Australian universities. In our study no differences were found between local and Asian students in ratings of perceived seriousness or understanding of plagiarism. However, significant negative relationships were found between both seriousness and understanding, and self-reported plagiarism rates. This suggested that as perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 40 publications
5
67
0
1
Order By: Relevance
“…The NESB group did not have a clear understanding of what constitutes plagiarism, and showed less respect for the intellectual property of material on the web. In agreement with Marshall and Garry (2005) on the issue of proficiency, Maxwell, Curtis and Vardanega (2008) observed that Asian students not fluent in English had technical problems in writing, especially in terms of summarizing, synthesizing and rephrasing the ideas of others in various ways or styles. Essentially, the difficulty was caused by their inability to express ideas in English.…”
Section: English Proficiency and Internet Plagiarismsupporting
confidence: 85%
See 1 more Smart Citation
“…The NESB group did not have a clear understanding of what constitutes plagiarism, and showed less respect for the intellectual property of material on the web. In agreement with Marshall and Garry (2005) on the issue of proficiency, Maxwell, Curtis and Vardanega (2008) observed that Asian students not fluent in English had technical problems in writing, especially in terms of summarizing, synthesizing and rephrasing the ideas of others in various ways or styles. Essentially, the difficulty was caused by their inability to express ideas in English.…”
Section: English Proficiency and Internet Plagiarismsupporting
confidence: 85%
“…Since English is used quite a lot in Malaysian schools and universities as the language of teaching and learning, students who are incompetent in it would encounter some difficulty in getting their written assignments done. Many perhaps take the easy way out by copying and pasting information verbatim from the Internet and turning it into their term papers (Lahur, 2004;Marshall & Garry, 2005;Maxwell, Curtis, & Vardanega, 2008). How prevalent this practice is among secondary school students is yet to be known.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In some of these studies, Eastern culture is called "Orientalism/the Orient" and the East includes developing countries and the Third World; on the other hand, the West is called "the Occident" and includes developed countries (Leask, 2006, p.185). Asian countries are defined using concepts from the Confucian tradition (Chien, 2017;Maxwell et al, 2008). These studies not only place emphasis on cultural differences regarding plagiarism but they also argue that Western undergraduate students (from countries like the US, UK, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…have improved skills in individual and independent thinking, critical thinking and learning, as well as the ability to complete independent and unassisted research (Zimerman, 2012;, and that they place importance on rules of academic honesty, such as anti-plagiarism, and are sensitive in applying these rules (Chien, 2017;Zimerman, 2012;Leask, 2006). Most research regarding Eastern (Chien, 2017;Leask, 2006;Hayes & Introna, 2005), Confucian or Asian (Maxwell et al, 2008;Sowden, 2005) cultures reveals that students of these cultures are educated based on recitation, in which they memorise the knowledge provided, meaning students lack critical thinking skills. Researchers often define these students as superficial learners who do not fully consider the importance of plagiarism.…”
Section: Introductionmentioning
confidence: 99%
“…The survey, conducted in 2012 and2013, used an electronic questionnaire containing 30 multiple choice questions developed from principles and orientations conventionalized by the literature concerning plagiarism concept and definition (Australian Government, 2007;U.S. Department Of Health And Human Services, 2005;United Kingdom, 2011), occurrence modality (Roig, 2011;Green, 2002;Gilmore et al, 2010;Pecorari, 2003), types of plagiarism (Harris, 2001, Loui, 2002, Roig, 2011Vardanega, 2008;Plagiarism, 2013), reasons for occurrence Popal, 2011;Harris, 2001;Trevino, 1997;Mccabe, Butterfield & Trevino, 2006;Power, 2009;Sauthier et al, 2011), standards and preventive actions adopted (Pecorari, 2003;Trevino & Butterfield, 2001;Pavela, 2005). We identified that the fact of respondents agreeing or disagreeing with the theoretical-conceptual characteristics of plagiarism did not make a difference in their capacity of correctly assessing practical situations characterized as plagiarism.…”
Section: Apêndice B -Abordagem Do Plágio Nas Três Melhores Universidamentioning
confidence: 99%